Optimization of Biodiesel Production from Siberian Apricot (Prunus sibirica L.) Oil Using Response Surface Methodology - Wang, L.; Chu, J. (Asian Journal of Chemistry, 2012)
Response surface methodology, with central composite rotatable design, was used to explore optimum conditions for the transesterification of Siberian apricot oil. The effect of five-level four factors and their reciprocal interactions were studied. A total of 30 experiments was conducted and designed to study the effect of catalyst concentration, methanol/oil molar ratio, reaction temperature and reaction time on the biodiesel yield. A second-order polynomial regression model was fitted and found adequate with R2 of 0.9942. When the transesterification was carried out at 67 ºC, with a 7.3:1 methanol/oil molar ratio to Siberian apricot oil, a reaction time of 60 min and a catalyst amount of 1.18 % wt, the conversion of Siberian apricot oil was 92.9 %. The most fuel properties of Siberian apricot methyl esters were found to be within the EN 14214-2005 and ASTM D6751-2003 biodiesel standards.